From Worship to Folkloric Display: The Decontextualization and Transformation of the Semah Ritual in Turkish Cinema - Öztürk, Melisa (Journal of Alevism-Bektashism Studies, 2025)
This article examines how semah, one of the fundamental components of the cem ritual within the Alevi belief system, is represented in Turkish cinema, focusing on the ways in which this representation departs from its ritual context and is reconstituted with new meanings. The transformative nature of rituals, shaped by social processes such as migration, urbanization, politics, and cultural mobility, provides a conceptual framework for understanding the cinematic circulation of semah. Conceived as an integrated whole organized through the unity of word, melody, and service, the cem reveals the theological, mythical, and symbolic dimensions of semah, moving it beyond a purely corporeal sequence of movements.The study establishes its conceptual framework by addressing the mythical origins of semah, the narrative of the Kırklar, and Sufi interpretations, and by examining the spatial and functional transformations of rituals following the migration of Alevi communities from rural to urban settings. Within this historical context, cinematic representations are analyzed chronologically. While the earliest appearances of semah in the 1970s were shaped by folkloric aesthetics and censorship conditions, representations in the 1980s increasingly transformed the ritual into a symbolic and dramatic narrative element. In the 1990s, some films display a growing fidelity to ritual context, whereas others reinterpret semah at the level of personal ecstasy and metaphor. From the 2000s onward, semah is recontextualized in diverse ways—as a narrative of love, a marker of identity, an institutionalized performance, or a cinematic staging that renders traumatic memory visible. The findings demonstrate that the shift of semah from a sphere of worship to one of cultural performance can be traced through cinematic language, aesthetic choices, and narrative strategies.
Keywords: Semah; Cem; Ritual; Cinema; Alevism; Transformation; Representation